Sexual Dysfunction Related to Drugs: a Critical Review. Part V: α-Blocker and 5-ARI Drugs - Torre, A. La; Giupponi, G.; Duffy, D.; Conca, A.; Cai, T.; Scardigli, A. (Pharmacopsychiatry, 2016)
Sexual dysfunction is a potential side effect of BPH (benign prostatic hyperplasia) and LUTS (lower urinary tract symptoms) drugs: this article is a critical review of the current literature. Many studies have been published on this topic. Methodological flaws limit the conclusions of these studies, mainly because of the lack of diagnostic criteria for ejaculatory and sexual desire dysfunction. Few of these studies are RCTs.The α-blocker (also called α1-adrenergic antagonist, alpha-adrenoceptor antagonist, alpha-blocker or AB) and 5-ARI (also called 5α-reductase inhibitor or testosterone-5-alpha reductase inhibitor) drugs can in particular cause erectile dysfunction, ejaculatory disorders and reduction of sexual desire. The sexual side effect profile of these drugs is different. Among the α-blockers, silodosin appears have the highest incidence of ejaculatory disorders. Persistent sexual side effects after discontinuation of finasteride has recently been reported, however further studies are needed to clarify the true incidence and the significance of this finding.It is desirable that future studies include validated tools to assess and diagnose sexual dysfunction induced by these medications, especially for ejaculation and sexual desire disorders.Only a small amount of research has intentionally set out to investigate sexual dysfunction caused by α-blocker and 5-ARI drugs: studies to specifically assess sexual dysfunction induced by these drugs are needed. Further studies are also needed to assess in the long term the role of combined therapy of phosphodiesterase type 5 inhibitors and α-blockers or 5-ARIs in treating LUTS/BPH.Methods: This study was conducted in 2014 using the paper and electronic resources of the library of the “Azienda Provinciale per i Servizi Sanitari (APSS)” in Trento, Italy (http://atoz.ebsco.com/Titles/2793). The library has access to a wide range of databases including DYNAMED, MEDLINE Full Text, CINAHL Plus Full Text, The Cochrane Library, Micromedex healthcare series, BMJ Clinical Evidence. The full list of available journals can be viewed at http://atoz.ebsco.com/Titles/2793, or at the APSS web site (http://www.apss.tn.it).In completing this review, a literature search was conducted using the key words “benign prostatic hyperplasia drugs”, “lower urinary tract symptoms drugs”, “α-blockers”, “5-ARIs”, “sexual dysfunction”, “sexual side effects”, “treatment-emergent sexual dysfunction”, “phosphodiesterase type 5 (PDE5) inhibitors”. All resulting listed articles were reviewed. Studies published between 2002 and December 2014 were included in the review.We included all studies that explicitly reported data on sexual dysfunction during treatment with α-blockers and 5-ARIs. We also reviewed studies that have evaluated the use of phosphodiesterase type 5 (PDE5) inhibitors in combination with these drugs.The purpose was to identify possible intervention strategies for sexual dysfunction related to these drugs.
Keywords: α-blockers; 5-ARIs; benign prostatic hyperplasia (BPH) drugs; LUTS (lower urinary tract symptoms) drugs; sexual dysfunction; sexual side effects; treatment-emergent sexual dysfunction